2014
DOI: 10.1007/s11618-014-0479-4
|View full text |Cite
|
Sign up to set email alerts
|

Wirkungen zentraler Abschlussprüfungen im Mehrebenensystem Schule. Eine Zwischenbilanz internationaler und nationaler Befunde und Forschungsdesiderata

Abstract: We grant a non-exclusive, non-transferable, individual and limited right to using this document. This document is solely intended for your personal, non-commercial use. Use of this document does not include any transfer of property rights and it is conditional to the following limitations: All of the copies of this documents must retain all copyright information and other information regarding legal protection. You are not allowed to alter this document in any way, to copy it for public or commercial purposes,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
2
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 49 publications
0
5
2
1
Order By: Relevance
“…One finding that relates specifically to mathematics in Germany is that "students who take central exit exams in mathematics like mathematics less, think it is less easy, and are more likely to find it boring" (Jürges & Schneider, 2010, p. 497). On the other hand, Klein et al (2014) report predominantly positive results from various investigations concerning achievement gains in mathematics associated with centralized final examinations, although limitations of these results are emphasized.…”
Section: Previous Research Results On Study Ability and Centralized F...mentioning
confidence: 95%
See 3 more Smart Citations
“…One finding that relates specifically to mathematics in Germany is that "students who take central exit exams in mathematics like mathematics less, think it is less easy, and are more likely to find it boring" (Jürges & Schneider, 2010, p. 497). On the other hand, Klein et al (2014) report predominantly positive results from various investigations concerning achievement gains in mathematics associated with centralized final examinations, although limitations of these results are emphasized.…”
Section: Previous Research Results On Study Ability and Centralized F...mentioning
confidence: 95%
“…In a more recent study, Leschnig et al (2022) also demonstrated that centralized final examinations have a positive effect on adults' cognitive abilities, including numeracy literacy. Klein et al (2014) point out, however, that the term centralized final examination subsumes many inconsistent forms of assessments that differ, for example, in (de)centralized correction. Thus, Klein et al (2014) conducted a systematic review on the effect of examinations, that must be taken by all students in a given subject at the end of an educational period, which are proctored by an entity external to the school, and comprise the same externally determined tasks for all schools -criteria that are met by the Austrian SRP in mathematics for AHS and partially also for BHS.…”
Section: Previous Research Results On Study Ability and Centralized F...mentioning
confidence: 99%
See 2 more Smart Citations
“…Im beruflich strukturierten schweizerischen Arbeitsmarkt hat das berufsspe zifische Humankapital einen sehr grossen Stellenwert (Sacchi et al 2016 Hoch standardisierte Abschlussprüfungen sind zentral organisiert, lehrplanba siert und durch externe Behörden festgelegt (Klein et al 2014). Eine Reihe von Stu dien legt nahe, dass sich standardisierte Abschlussprüfungen positiv auf die Leistung der Lernenden auswirken (Effinger und Polborn 1998;Woessmann 2002Woessmann ,2003Woessmann ,2010Lüdemann 2011;Leschnig 2017).…”
Section: Die Schweizerische Berufsbildungunclassified